Online Business Development And Contribution Toward Local Economic In Rural Areas - Ahmad Farhan; Oktavianty Oktavianty; Wahid Wahid (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
Online business have become one of the most trending form of business nowadays, this form of business require very little cost of operation. Despite of its advantage in term cost, online business require its owner to have a technology readiness in order to successfully operate the business. There numerous factor that ensure the success of online business, factors such the design of promotion site, quality of services, and the method of payment is very important for the success of online business. There are also few aspect to pay attention to before building and in process of developing online there are also few aspect that is fundamental for this form of business. These factor are including early market research, market and digital literacy, starting point and innovation, choice of product, tracking and monitoring, and lastly business partnership. Its important to note that the right decision should contribute to positive impact as well. The purpose of this paper is to discover the influence of numerous factors affecting the success of online business. Further, this paper will also explain how online business have contribute to local economic especially in rural areas. The finding of this paper are expected to contribute in further development of online business especially in rural area where people aren’t yet familiar with digital transformation.